كتاب الترجمة بالمدخل البنائي فى الدورة التدريبية العربية - Miftahul Maesaroh (Abjadia, 2016)
تتشكّل المواد الدّراسية عنصرًا أساسيًا من مكوّنات المنهج الدّراسيّ. وكذلك اليوم أنّ دراسة الترجمة تصبح دراسة مهمّة لتعلّمها لاسيما فى عصرنا الحديث كانت العلوم متطوّرة فى أيّ مجال. فبهذه الرسالة تقصد الباحثة تطوير المواد الدراسيّة خاصًا فى مجال التّرجمة بالمدخل البنائي للدّورة العربية بتطبيها فى دورة "الأزهار" بباري كاديري. وكانتأسئلة البحث فى هذه الرسالة يتكوّن من البنود الأتية: 1) كيف يتم تطوير مواد الترجمة بالمدخل البنائي 2) ما مميزات مواد الترجمة المطوّرة بالمدخل البنائي 3) ما مدى فعالية مواد الترجمة المطوّرةبالمدخل البنائي،التى كانت بتطبيقها فى الدورة العربية "الأزهار" بباري كاديري. وأهداف البحث يعنى1) لكشف إتمام تطوير مواد الترجمة بالمدخل البنائي 2) لكشف مميزات مواد الترجمة المطوّرةبالمدخل البنائي 3) لكشف مدى فعالية مواد الترجمة المطوّرةبالمدخل البنائي فى الدورة العربية "الأزهار" بباري كاديري. والمنهج المستخدم فى هذا البحث هو منهج البحث والتطوير نموذج "Borg and Gall". فحصلت الباحثة نتيجة البحث أنّ تعليم التّرجمة لترقية المحادثة باستخدام الكتاب المطوّر بالمدخل البنائي لمرحلة المبتدئين يؤثّر تأثيرًا فعاليًا لدى طلبة دورة "الأزهار" بباري كاديري. يؤكّد بأنّ درجة (ttabel) (thitung) أو بعبارة أنّ تاء حساب أكبر من تاء جدول، هذا يدلّ على أنّ HO مردود و Haمقبول.Teaching material is a basic element of the learning curriculum component. At this time, the study of translation becomes crucial to be studied along with the development of science in various areas. This thesis is intended researchers to develop teaching materials translation using constructivist approach for Arabic language courses were implemented in the course of Arabic "Al-Zhar" Pare. The problems of this study include: 1) how the process of developing teaching materials translation of the constructivist approach in Arabic language courses "Al-Azhar" Pare? 2) What are the characteristics of teaching materials that have been developed by the constructivist approach in Arabic language courses "Al-Azhar" Pare? 3) How is the effectiveness of teaching materials that have been developed by the constructivist approach in Arabic language courses "Al-Azhar" Pare ?. The purpose of the study as follows: 1) to uncover the process of developing teaching materials constructivist approach in translation with Arabic language courses "Al-Azhar" Pare? 2) to reveal the characteristic of teaching materials that have been developed by the constructivist approach in Arabic language courses "Al-Azhar" Pare? 3) to reveal the effectiveness of teaching materials that have been developed by the constructivist approach in Arabic language courses "Al-Azhar" Pare? The method used in this research is "Research and Development" model Borg and Gall. The results of the study of learning by using teaching materials translation of the constructivist approach has the effect for students in Arabic language courses "Al-Azhar" Kediri. These results are corroborated by evidence that the results of the analysis thitung  t table  (thitung bigger than t table ) shows that H0 rejected and Ha accepted.